.Evaluation of National Quality Control Capacity for Herbal Medicines in West Africa: The Case of Benin and Burkina Faso. - ASSANHOU, Assogba Gabin (My University, 2020)
Objective: To assess the capacity of quality control of herbal medicines in two countries in West Africa, thus, Benin and Burkina Faso. Methods: This is a cross-sectional descriptive study, through surveys of 33 manufacturing facilities and 5 independent quality control laboratories listed in the two countries. Results: Among the 33 production units surveyed, only six had space or premises dedicated to quality control. Furthermore, 29 out of the 33 manufacturers used geographic, organoleptic and macroscopic criteria to verify the quality of the raw materials when buying or harvesting. For finished products, they checked the organoleptic characteristics themselves. For more complex analysis, such as the search for microbial contaminants or pesticide residues, they most often used public laboratories at the national level, which are better equipped with skilled staff. Conclusion: These results show that a lot of effort needs to be done in this area by these two countries in order to better ensure the quality and safety of locally produced herbal medicines.
Keywords: Herbal medicine; traditional medicine; raw materials; quality control; Benin; Burkina Faso.